The Estimated Carbon Stock in Palm Oil Plantations at PT. Sinar Gunung Sawit Raya, North Sumatra - Anggraini, Sari; Tampubolon, Owen Martinus; Tiara (Agrotekma: Jurnal Agroteknologi dan Ilmu Pertanian, 2024)
The aim of this research is to determine the estimated carbon stock stored in oil palm plants at PT. Sinar Gunung Sawit Raya, Manduamas District, Central Tapanuli. This research was carried out in April-July 2024 and used a descriptive design with a quadratic transect sampling method for sampling carbon estimates. Observations on sample plots are in accordance with differences in land conditions, namely oil palm in areas around the coast, areas around Jabon industrial plants and areas around community settlements. The biomass of oil palm plant in the area around the coast is 2.1620 tons/ha, in the area around industrial plants it is 2.2918 tons/ha, and in the area around community settlements it is 2.2061 tons/ha. From the results of this research carbon reserves Oil palm (Elaeis guineensis Jacq) areas around Jabon industrial plants are larger than areas around the coast and areas around residential areas.